Camptothecin-Based Regimens for Treatment of Ewing Sarcoma: sPast Studies and Future Directions. (6th April 2011) - Wagner, Lars
Abstract : New therapies are needed to improve survival for patients with Ewing sarcoma. Over the past decade, camptothecin agents such as topotecan and irinotecan have demonstrated activity against Ewing sarcoma, especially in combination with alkylating agents. Previous studies have shown camptothecin-based combinations to be tolerable outpatient strategies that are attractive for salvage therapy. This paper highlights important issues related to drug dosing, schedule of administration, pharmacokinetics, toxicity, and activity of commonly used camptothecin-based regimens. Also discussed are strategies for incorporating these regimens into therapy for newly diagnosed patients, including several potential possibilities for combination with targeted agents.